PENINGKATAN DAYA SAING DAN KESEJAHTERAAN KT. KOMPITU HIJAU SEBAGAI GARDEN CITY MELALUI DIGITAL MARKETING - Asteria, Beta; Sulastiningsih, Sulastiningsih; Subkhan, Muhammad; Renaldy, Fatkhan; Abdillah, Anang (LPPM Universitas Nusa Mandiri, 2024)
KT Kompitu Hijau faces challenges in marketing fresh agricultural products only through Whatsapp Group. Marketing of derivative products such as vegetable chips, healthy vegetable juice, dawet spinach, instant herbal medicine is limited to certain events organized by the Department. As well as less than optimal production management related to less attractive product packaging and water and electricity problems. The solution to overcome these problems requires training and mentoring in Digital Marketing as well as training and mentoring in production management. The method used in the training and mentoring of Digital Marketing and Production Management is the Participatory Rural Appraisal (PRA) approach which involves the community in the development process. As well as the FGD method to determine the right marketing strategy. The results after carrying out community empowerment activities are KT. Kompitu can market and sell products online through GrabMart E-Commerce, Instagram and WhatsApp Business Toko Kompitu Sehat. The results of assistance and training in production management of KT Kompitu Hijau are able to produce products that are packaged and have an attractive logo. As well as having optimal waters to produce the best products. KT Kompitu Hijau won 1st place in the Yogyakarta City Vegetable Landscape Competition which was attended by 34 farmer groups in Yogyakarta City. The evaluation results show that digital literacy has increased. This community empowerment activity was organized as a contribution to increasing the competitiveness and welfare of KT. Kompitu Hijau.